Freedom: A Documentary History of Emancipation, 1861-1867 : Series 3, Volume 2: Land and Labor, 1866-1867 - West, Stephen A., 1965-; Rowland, Leslie S.; O'Donovan, Susan E.; Miller, Steven F.; Masur, Kate; Kaye, Anthony E.; Hayden, Rene (Book collections on Project MUSE., 2013)
This volume examines the remaking of the South's labour system in the tumultuous aftermath of emancipation. Using documents selected from the National Archives, this volume depicts the struggle of unenfranchised and impoverished ex-slaves to control their own labour, establish their families as viable economic units, and secure independent possession of land.